Detection of Neorickettsia sp. in Oligoryzomys flavescens rodent from a protected urban area in Buenos Aires City (Argentina) - Cicuttin, Gabriel L. (2022)
Rodents play an important role in vector-borne pathogens cycle. To detect Anaplasma, Ehrlichia, Neorickettsia, Rickettsia and Borrelia species in rodents from a protected urban area in Buenos Aires City (Argentina) were analyzed 203 organ pools of Mus musculus, Oligoryzomys flavescens, Rattus norvegicus, Deltamys kempi and Scapteromys aquaticus by PCR. Only one O. flavescens (1.2%) was positive by PCR for 16S rRNA fragment for the Anaplasmataceae family and the sequence had 99.7% identity with Neorickettsia risticii. Plus, the sequence obtained for a fragment of the p51 gene for the genus Neorickettsia from positive sample had 95.3–96.1% identity with N. risticii found previously in bats Tadarida brasiliensis from Buenos Aires City. Our study presents the first finding of Neorickettsia in rodents from natural environment, but further studies are necessary about these vector-borne bacteria and the rol of rodents in its epidemiology.